Improving Speaking Skills with the Impromptu Method in the MBKM Programs - Diyah Mahmawati Mahmawati (Mastery: Master of English Language Journal, 2023)
This study investigates the effectiveness of implementing the Impromptu Method to enhance speaking skills among students enrolled in the MBKM (Merdeka Belajar Kampus Merdeka) programs at STIT Miftahul Midad Lumajang. With the increasing importance of effective communication in the globalized world, it has become imperative for higher education institutions to equip their students with proficient speaking abilities. The Impromptu Method is chosen for its emphasis on spontaneity and quick thinking, which are valuable skills in various professional and academic contexts. The research methodology involves a pre-test and post-test design, where participants' speaking skills are assessed before and after the implementation of the Impromptu Method. Additionally, qualitative data in the form of student feedback and observations are collected to gain insights into their experiences with the method. The study aims to analyze the impact of the Impromptu Method on students' confidence, fluency, and articulation in spoken communication. Preliminary findings suggest that the Impromptu Method holds promise as an effective pedagogical approach to enhance speaking skills. Students report increased self-assurance in impromptu speaking situations, improved fluency, and the ability to articulate their thoughts more coherently. The study provides valuable insights into the potential benefits of incorporating this method into the MBKM programs, ultimately contributing to the development of well-rounded, confident, and proficient speakers among students at STIT Miftahul Midad Lumajang.